ANALISIS KINERJA GURU PAI DALAM PENERAPAN METODE PROMPTS PADA PENYANDANG DISABILITAS DI SLB A YAPTI MAKASSAR - Ali, Nur Aliah; Tanasy, Novalia (Universitas Islam Negeri Alauddin Makassar, 2018)
This study is aim to determine the ability and skills of Islamic education teachers in applying prompts methods for students with disabilities A or blind students.The specific purpose is to find out the performance of the Islamic education teacher in applying thetypes of prompts in the form ofverbal prompts, gestural prompts, modeling prompts and physical prompts, beside that this study is determine too the factors that influence the performance of Islamic education teachers in applying the prompts method to students with disabilities A in SLB A YAPTI Makassar especiallyfor the subject Thaharah, Prayer and Read and write the Qur'an.The research method used is field research with descriptive qualitative and quantitative analysis. In this study, the data collection methods used are observation, interviews, and documentation. The collected data will be analyzed usingan interactive model of Mile and Huberman which includes data reduction, data presentation, verification and conclusion drawing. The type of qualitative data will be analiyzed by deductive-inductive conclusions and quantitative data analyzed using descriptive quantitative in the form of percentages and performance scoring based on the performance scoring table.The research results obtained areThe teacher's performance level are at varying levels. namely moderate, high and very high. NH teachers have a performance at a score of 4 or very high level which means applying all types of prompts in Islamic learning process. RM teachers have a performance at a score of 3 or high level that applies 3 prompts while the KS teacher is on a score of 2 or medium level which only applies two types of prompts namely verbal and physical prompts only. Differences The use of types and indicators applied by Islamic education teachers is different due to material factor, student and teacher characteristics factors.